2005
DOI: 10.1167/iovs.04-1483
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Secreted Protease fromPseudomonas aeruginosathat Causes Corneal Erosions

Abstract: PASP is a protease that has not been previously identified. It causes corneal epithelial erosions, indicating its likely activity as a virulence-promoting factor in Pseudomonas keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 51 publications
4
69
0
2
Order By: Relevance
“…As previously reported by Purschke et al (2012), we observed a significant increase in the production of iron-regulated proteases by P. aeruginosa in coculture supernatants, including PrpL, PasP, AprA and a hypothetical protein zinc-protease, PA0572 (Supplementary Table S3) (Wilderman et al, 2001;Marquart et al, 2005). These proteins are known for their strong proteolytic activities, which are responsible for rupturing tight junctions in the epithelium, leading to tissue invasion and bacterial spreading (Azghani et al, 1993).…”
Section: Interspecies Competition Triggers Virulencesupporting
confidence: 78%
“…As previously reported by Purschke et al (2012), we observed a significant increase in the production of iron-regulated proteases by P. aeruginosa in coculture supernatants, including PrpL, PasP, AprA and a hypothetical protein zinc-protease, PA0572 (Supplementary Table S3) (Wilderman et al, 2001;Marquart et al, 2005). These proteins are known for their strong proteolytic activities, which are responsible for rupturing tight junctions in the epithelium, leading to tissue invasion and bacterial spreading (Azghani et al, 1993).…”
Section: Interspecies Competition Triggers Virulencesupporting
confidence: 78%
“…aeruginosa is capable of secreting at least 7 different proteases including elastase A and B, modified elastase, alkaline protease, protease IV, P. aeruginosa small protease and large exoprotease, some of which play a potential role in the pathogenesis of keratitis [113,202]. Metalloproteases especially elastase B (Las B) and alkaline protease (AP), play a considerable role in keratitis as Las B injection into the corneal stroma result in significant corneal damage [73,88].…”
Section: Bacterial Invasion and Cytotoxic Effectsmentioning
confidence: 99%
“…Other protease bands were either weak or not visible in the low-proteaseproducing strains and the gelatinolytic band in lane 5 (Fig. 4) with an apparent molecular mass of~80 kDa was most likely PASP (Marquart et al, 2005). Protease IV activities in P. aeruginosa culture supernatants were determined (Table 2).…”
Section: Detection Of Protease IV In Clinical Isolatesmentioning
confidence: 99%
“…The virulence factors most commonly associated with P. aeruginosa-induced ocular damage are exo-enzymes S (exoS) and U (exoU) (Fleiszig et al, 1997), elastase (lasB) (Kessler & Blumberg, 1987), alkaline protease (aprA) (Twining et al, 1993) and protease IV (piv) (O'Callaghan et al, 1996). Another protease, P. aeruginosa small protease (PASP), can also cause rapid corneal damage (Marquart et al, 2005). Other important pathogenic mechanisms include the genes involved in translocation and activation of virulence proteins via the type II (xcp) and type III secretory pathways (Sandkvist, 2001;Yahr et al, 1997).…”
Section: Introductionmentioning
confidence: 99%